Efek Suplementasi Omega 3 dan Latihan Fisik Terhadap Respon Inflamasi - Novadri Ayubi; Bambang Purwanto; Purwo Sri Rejeki (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
The aims of this article is to find out how the effects of omega 3 supplementation and physical exercise on the inflammatory response. The method applied is literature review. The results showed that omega 3 supplementation and regular exercise can reduce the inflammatory response that is not controlled. Inflammation is a protective response caused by injury or tissue damage. After physical activity the body will experienced an increase in inflammatory markers, namely C-Reactive Protein (CRP), Interleukin 1 (IL-1), Interleukin 6 (IL-6), Interleukin 10 (IL-10) and Tumor Necrosis Factor-a (TNF-a). Physical exercise, especially high-intensity eccentric exercises, will cause damage to muscle fibers and delayed muscle pain (DOMS) which results in disruption to muscle strength. Muscle pain is caused by an inflammatory process due to increased levels (TNF-a) in response to muscle damage. Inflammatory response that is not controlled can be controlled by giving omega 3 supplementation. It can be concluded that omega 3 supplementation and regular exercise are proven to reduce the inflammatory response that is not controlled, soto reduce the intensity of pain which support the performance in carrying out the exercise program.